How Do School District Boundary Changes and New School Proposals Affect Housing Prices - Xiaozhou Ding; Christopher Bollinger; Michael Clark; William H. Hoyt (Center for Economic Studies and ifo Institute (CESifo), 2020)
In the past fifty years, a voluminous literature estimating the value of schools through capitalization in home prices has emerged. Prior research has identified capitalized value using various approaches including discontinuities caused by boundaries. We use changes in school boundaries and the proposal of a new school. Our findings from redistricting in the Fayette county school district (KY) show that prices for homes redistricted from a lower-performing (based on test scores) school into the proposed school catchment area increase by six percent. For houses in higher-performing school catchment areas redistricted to the proposed new school district, there is a smaller increase in value. Houses redistricted from higher-performing schools to lower-performing schools decrease in value by three to five percent. However, many of the redistricted properties see little or no significant change, suggesting that only extreme changes in school quality are capitalized. We estimate that homes in the redistricted areas increased by 108 million relative to homes that were not redistricted.
Keywords: D10; I20; R30; 330; property values; hedonics; school quality; school district; difference-in-differences